Preparation of ZnO/CNC Nanocomposite and Evaluation of Photocatalytic Activity in Various Organic Dyes - Kyu Hong, Sung; Hwi Cho, Bum; Bae Ko, Weon (Asian Journal of Chemistry, 2012)
Zinc oxide nanoparticles (ZnO) were synthesized by an aqueous alcoholic reaction between zinc nitrate and sodium hydroxide under ultrasonic irradiation at room temperature and their photocatalytic activities were examined using various organic dyes. To fabricate the ZnO/ carbon nanocolloid (CNC) nanocomposite, ZnO and carbon nanocolloid were heated in an electric furnace at 700 °C for 2 h. The optical properties of the unheated ZnO/CNC (UH-ZnO/CNC) and heated ZnO/CNC (H-ZnO/CNC) nanocomposites were characterized by X-ray diffraction, scanning electron microscopy and transmission electron microscopy. The photocatalytic activities of the unheated-ZnO/CNC and heated-ZnO/CNC nanocomposites to degrade organic dyes, such as methylene blue, rhodamine B, methyl violet and methyl green under ultraviolet light at 365 nm were examined by UV-VIS spectroscopy. The heated-ZnO/CNC nanocomposite showed more efficient photocatalytic activity in the degradation of various organic dyes than the unheated-ZnO/CNC nanocomposite, especially with the degradation of methylene blue.